Лінгводидактична модель навчання молодших школярів образотворчої діяльності (малювання) засобами англійської мови - Фрумкіна Арина; Frumkina Aryna (Видавництво «Код», 2025)
Резюме. У статті представлено результати теоретичного обґрунтування та експериментальної перевірки лінгводидактичної моделі навчання молодших школярів образотворчої діяльності (малювання) засобами англійської мови. Актуальність дослідження зумовлена необхідністю пошуку ефективних форм інтегрованого навчання, які забезпечують одночасний розвиток художньо-образотворчих і мовленнєвих умінь.

Abstract. The article presents the results of theoretical substantiation and experimental verification of a linguodidactic model for teaching primary school pupils visual arts (drawing) through the English language. The relevance of the study arises from the need to find effective forms of integrated learning that ensure the simultaneous development of artistic and linguistic competencies. The theoretical foundation of the model is based on the principle of procedural integration, which combines different educational components within one learning process, specifically artistic and speech activities. The model structure consists of five sequential stages: contour, linear, objectdepictive, object-compositional, and plot-depictive. Each stage unites the development of artistic skills with gradual linguistic advancement. The experimental research was carried out in three stages – diagnostic, formative, and control – involving first- and second-grade pupils from general secondary schools i. During the formative stage, a system of integrated lessons was implemented, where pupils performed artistic actions (drawing, decorating, creating visual compositions) combined with English-language commentary, description, and dialogue. The experiment demonstrated a 26% increase in the level of artistic skills and a 21% increase in linguistic performance. The results confirmed significant improvement in creativity, communicative initiative, motivation, and emotional engagement. It was proved that procedurally integrated learning creates conditions for the harmonious development of cognitive, emotional, and linguistic spheres of younger learners. The proposed model demonstrated validity, reproducibility, and potential for implementation in primary education and in the professional training of future teachers.
Linguodidactic model for teaching primary school pupils visual arts (drawing) through the english language
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: інтегроване навчання; лінгводидактична модель; образотворча діяльність; малювання; англійська мова; молодші школярі